2020
DOI: 10.30659/e.5.1.1-13
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical problems encountered by teachers of English to Computer Science students in the Indonesian context

Abstract: Many factors are required in order to increase the skills of English of higher education students, specifically computer science students. Of the factors, teachers play a very important role since they are the agents of change in the classrooms; not to neglect that the students are also the agents of their own changes. Using Brown’s 12 pedagogical characteristics of a good language teacher as its theory, this is a report of the first step of design-based research, practical problems encountered by teachers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…English learning materials which can be applied in the future profession especially in computer network engineering field. The findings of this study support the idea of using appropriate learning materials as an important part of instructional strategies that ought to be noticed by teachers of English to computer science within Indonesian context (Lestariningsih, Madya, & Nurkamto, 2020). The findings are also in tune with the notion stating that such visual aspects of learning materials as font size, layout, and illustration as well as glosses or vocabulary lists are among the factors that make a learning materials acceptable (Irwansyah, 2019).…”
Section: Results and Discussion The Learning Needs Of The Computer Nesupporting
confidence: 83%
“…English learning materials which can be applied in the future profession especially in computer network engineering field. The findings of this study support the idea of using appropriate learning materials as an important part of instructional strategies that ought to be noticed by teachers of English to computer science within Indonesian context (Lestariningsih, Madya, & Nurkamto, 2020). The findings are also in tune with the notion stating that such visual aspects of learning materials as font size, layout, and illustration as well as glosses or vocabulary lists are among the factors that make a learning materials acceptable (Irwansyah, 2019).…”
Section: Results and Discussion The Learning Needs Of The Computer Nesupporting
confidence: 83%
“…As EFL student teachers are still on their way to become EFL teachers that one day will be the agents of change (Lestariningsih et al, 2020), their beliefs will also influence their way of teaching and future students' learning. Due to their lack of experience in teaching, they might hold negative or unrealistic beliefs towards teaching and learning which might transform into their teaching.…”
Section: Introductionmentioning
confidence: 99%
“…With its importance for language learning, pedagogical knowledge of technology integration in language classroom is a competency that educators in the twenty-first century must have and should be enormously spotlighted in teacher training programs and professional development (Lestariningsih et al, 2020;Galvis, 2012). However, some previous researches reported that EFL teachers have not been equipped well with sufficient support of digital learning skills, such as using computer tools or software program (Celik, 2013;Nordin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%